Effect of Laparoscopic Adjustable Gastric Banding on Metabolic Syndrome and Its Risk Factors in Morbidly Obese Adolescents. (7th November 2010) - Conroy, Rushika; Lee, Eun-Ju; Jean, Amy; Oberfield, Sharon E.; Sopher, Aviva; Kiefer, Krystina; Raker, Courtney; McMahon, Donald J.; Zitsman, Jeffrey L.; Fennoy, Ilene
Abstract : We examined the effect of laparoscopic adjustable gastric banding (LAGB) on weight loss, inflammatory markers, and components of the Metabolic Syndrome (MeS) in morbidly obese adolescents and determined if those with MeS lose less weight post-LAGB than those without. Data from 14–18 yr adolescents were obtained at baseline, 6 and 12 months following LAGB. Significant weight loss and improvements in MeS components were observed 6 months and one year following LAGB. The incidence of MeS declined 56.8% after 6 months and 69.6% after 12 months. There was no significant difference in amount of weight lost post-LAGB between those with and without MeS at either timepoint. Correlations between change in weight parameters and components of MeS in those with and without MeS at baseline were examined and found to vary by diagnostic category. LAGB is effective for short-term improvement in weight, inflammatory markers, and components of MeS in morbidly obese adolescents.